Producing Garments for Global Markets: Corporate Social Responsibility (CSR) in Myanmar's Export Garment Industry 2011–2015 - Jinsun Bae (Copenhagen Business School (CBS), 2018)
A growing number of the multinational enterprises work with a global network of suppliers that undertake production activities on their behalf. These enterprises operationalize CSR by enforcing corporate codes of conduct in their networks. The export garment industry of Myanmar—a country emerging out of economic sanctions imposed by Western countries—is no exception to this CSR trend. International fashion brands and retailors (called buyers) have sought out garment manufacturers in Myanmar, with the capacity to implement their social and environmental demands laid out in buyer-designated codes of conduct. This buyer requirement of CSR has taken many manufacturers by surprise because they were previously unaware of it. To some, suppliers CSR itself has been a novel term, and to others, some provisions of the code of conduct seemed to contradict local ways of taking responsibility for workers and local communities. Against this background, the manufacturers and various stakeholders of Myanmar's export garment industry have begun to discuss what CSR means and how should one practice it. This dissertation aims to answer the question of how and why has corporate social responsibility (CSR) been introduced, embraced and challenged in Myanmar's export garment industry during the period 2011 to 2015? The chosen empirical and temporal setting is highly suitable to examine the contestation of different CSR understandings exhibited by actors such as international buyers sourcing garments from Myanmar, and garment manufacturers and international donors in Myanmar. This study combines the global production network (GPN) analysis and institutional theories as analytical lens.
hdl:10398/9673
Keywords: 650